Purification and crystallization of coconut globulin cocosin from Cocos nucifera - Balasundaresan, D.; Sugadev, R; Ponnuswamy, M.N.
Cocosin is a legume class reserve protein found in coconut endosperm. Using coconut endosperm, two methods of purification were done. Crystallization was achieved by vapor diffusion (hanging drop)method using MPD, PEG 3350 and PEG 4000 as precipitants. X-ray diffraction data to 3.5-Å resolution were collected using Mar345 image plate detector system. Crystals of cocosin grown under 20
Keywords: STORAGE PROTEIN; COCONUT ENDOSPERM; COCOSIN; PURIFICATION; CRYSTALLIZATION; SPACE GROUP R3